A study on tandem photoanode and photocathode for photocatalytic formaldehyde fuel cell. (20th August 2020) - Wang, Yanming; Lan, Yalin; Bu, Degang; Qian, Bingzhi; Wang, Yang; Wang, Baoxin; Wu, Qiong; Li, Shuo; Zhang, Yu; Song, Xi-Ming
Abstract: We report a fuel cell device with double-side semiconductor photoelectrode, in which TiO2 nanorods (NRs) array serves as photoanode for formaldehyde oxidation, and Cu2 O photocathode takes part in oxygen reduction reaction (ORR). Unlike traditional noble metal-based fuel cells, the whole fuel cell reaction is operated from photoelectrocatalytic process due to photogenerated holes and electrons. The best performance is obtained by photoexciting both TiO2 photoanode and Cu2 O photocathode through contrast experiments, the short circuit current and open circuit voltage of the fuel cell reach 1.2 mA/cm 2 and 0.58 V, respectively. Mott-schottky measurement, surface photovoltage (SPV) transients and linear sweep voltammetry (LSV) test under illumination further reveal the thermodynamic and dynamic feasibility for charge transfer in the formaldehyde oxidation-oxygen reduction process. This study introduces an alternative design in developing non-noble metal photocatalytic fuel cells with low cost and high practicality. Graphical abstract: Image 1 Highlights: A non-noble metal photocatalytic formaldehyde fuel cell was designed and fabricated. Tandem TiO2 photoanode and Cu2 O photocathode give rational charge transfer path. The SPV transients reveal the conductivity type and kinetic information. Energy band diagram of the whole photocatalytic fuel cell is built.